The European Convention on Human Rights and the conflict in Northern Ireland - Dickson, Brice (Oxford : Oxford University Press, 2010)
Charting the role played by the European Convention on Human Rights during the conflict in Northern Ireland from 1968 to the present day, this text offers a systematic case-study of the Convention's capacity to protect human rights in a society wracked by terrorism and political conflict.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights -- Northern Ireland; Convention for the Protection of Human Rights and Fundamental Freedoms (1950); Social conflict -- Northern Ireland; Northern Ireland -- Politics and government -- 1969-1994.